Abusive endings: separation and divorce violence against women - DeKeseredy, Walter S. (Gender and justice, 2017)
"Abusive Endings offers a thorough analysis of the social-science literature on one of the most significant threats to women's health and well-being today--abuse at the hands of their partners. The authors provide a moving description of why and how men abuse women in myriad ways during and after a separation or divorce. The material is punctuated with the stories and voices of both perpetrators and survivors of abuse, as told to the authors over many years of fieldwork. Written in a highly readable fashion, this book will be a useful resource for researchers, practitioners, activists, and policy makers"--Provided by publisher